The Effect of Solidification Rate on the Microstructure and Mechanical Properties of Pure Magnesium - Murtatha M. Jamel; Hugo Lopez; Benjamin Schultz; Wilkistar Otieno (Metals, 2021)
Magnesium, Mg, has been widely investigated due to its promising potential as magnesium alloys for various applications, particularly as biomedical implantation devices among other medical applications. This work investigates the influence of different cooling rates on the strength of pure Mg. The cooling rates were set to cover a low cooling rate LCR (0.035 °C/s) in an insulated furnace, a moderate cooling rate MCR (0.074 °C/s) in uninsulated-ends furnace, and a high cooling rate HCR (13.5 °C/s) in liquid CO2. The casting process was accomplished using a closed system of melting and cooling due to the reactivity-flammability of magnesium in order to minimize processing defects and increase the safety factor. The as-cast samples were metallographically examined for their microstructure, and properties such as impact strength, hardness, and tension were determined. Increasing the solidification rate from 0.035 °C/s to 0.074 °C/s increased the hardness from 30 to 34 Rockwell Hardness and the UTS from 48 to 67 MPa. A higher solidification rate of 13.5 °C/s further enhanced the hardness to 48 Rockwell Hardness and the UTS to 87 MPa in comparison to the 0.074 °C/s cooling rate. Additionally, the fracture behavior and morphology were investigated. It was found that in general, the mechanical properties tended to improve by refining the grain structure.